The acquisition and development of cognitive skills and strategies: I. Making the butterflies fly in formation - Hanton, S.; Jones, G. (The Sport Psychologist, 1999)
This study extends the findings of previous research that elite performers, compared to nonelites, interpret their pre-performance cognitive and somatic anxiety symptoms as more facilitative than debilitating to performance. In-depth interviews were conducted with male elite swimmers (N = 10) and content analyzed. It was concluded that participants' skills and strategies were acquired via natural learning experiences and various education methods. Four areas of developmental themes throughout the swimmers' careers were revealed. They are listed here. Implication: There are mental skills that need to be learned and practiced to facilitate good competitive performances.